2011
DOI: 10.7556/jaoa.2011.111.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Osteopathic Manipulative Treatment for the Treatment of Hospitalized Premature Infants With Nipple Feeding Dysfunction

Abstract: Premature newborns and infants are usually required to successfully transition from gavage to nipple feeding using breast or bottle before discharge from the hospital. This transition is frequently the last discharge skill attained. Delayed acquisition of this skill may substantially prolong hospital length of stay. The authors describe a case of hospitalized premature twins who had considerable delays in attaining nipple-feeding skills. Because of their inability to take all feedings by nipple, preparation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 16 publications
1
29
0
1
Order By: Relevance
“…Although OMT has been barely studied in the care of premature infants [1416] our findings are consistent with the results of the exploratory study by Pizzolorusso and the recently published trial by Cerritelli. LOS reduction in the RCT by Cerritelli et al [14] was higher than that found in the present trial (−5.91; −7.94, −3.87; P < 0.001 versus −2.03; −3.15, −0.91; P < 0.01), but this difference is smaller in the group of infants who received early OMT (−5.91; −7.94, −3.87; P < 0.001 versus −4.16; −6.05, −2.27; P < 0.001) and might be related to the different characteristics of the samples under study.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Although OMT has been barely studied in the care of premature infants [1416] our findings are consistent with the results of the exploratory study by Pizzolorusso and the recently published trial by Cerritelli. LOS reduction in the RCT by Cerritelli et al [14] was higher than that found in the present trial (−5.91; −7.94, −3.87; P < 0.001 versus −2.03; −3.15, −0.91; P < 0.01), but this difference is smaller in the group of infants who received early OMT (−5.91; −7.94, −3.87; P < 0.001 versus −4.16; −6.05, −2.27; P < 0.001) and might be related to the different characteristics of the samples under study.…”
Section: Discussionsupporting
confidence: 90%
“…Very little research has been conducted looking at the effects of osteopathic manipulative treatment (OMT) on preterm infants [1416]. In the setting of the NICU, data suggests that OMT improves gastrointestinal function [15], reduces hospital stay [14, 15], and enhances nipple feeding function [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies and case reports starting shedding positive light on the effect of OMT on neonatal care. Lund et al [2] and Wescott [3] showed a possible effect of osteopathic procedures in the management of sucking dysfunctions. Similarly, Andreoli et al [4] suggested that OMT can be used as an adjuvant treatment for clubfoot complications, whilst Friedman [5] corroborated the application of osteopathy in reducing gastrointestinal problems, such as colics and regurgitation.…”
Section: Introductionmentioning
confidence: 99%
“…The present systematic review found a variety of studies and the aim of this paper was to summarize the evidence of using osteopathic medicine as diagnosis and to evaluate the effectiveness of OMT as an adjunct treatment option for infants in the NICU. Ten articles were found addressing the use of OMT in the NICU, six studies favored OMT and showed a positive effect [10,[12][13][14][15][16], one showed a negative effect [17], two did not report any between group comparisons [11,18], and the remaining one describes a study protocol and the study results have not yet been published [19].…”
Section: Discussionmentioning
confidence: 99%